Investigation of biosorption of chromium(VI) on Cladophora crispata in two-staged batch reactor - Aksu, Z; Ozer, D; Ekiz, HI; Kutsal, T; Caglar, A (Selper Ltd, Publications Div, 1996)
In this study, the adsorption of chromium(VI) to C. crispata was investigated in a two-staged batch reactor. The sorption phenomenon was expressed by the Freundlich adsorption isotherm and this expression was used for the calculation of the equilibrium value of the residual or adsorbed chromium(VI) concentration(C-eq or C-xeq) at each stage for a given ''quantity of alga/volume of waste water containing chromium(VI)'' or (X(o)/V-o) ratio in a two-staged batch reactor. Experimental C-eq values were compared to calculated ones at each stage. Applications in waste water treatment for chromium(VI) removal have been suggested.
Keywords: C-crispata; chromium(VI) adsorption; two-staged batch reactor; separation process